PRODUCTION STRUCTURE OF MAIN COMMERCIAL TREE SPECIES IN A MANGROVE FOREST IN EAST SUMATERA, INDONESIA - CECEP KUSMANA (SEAMEO BIOTROP, 1992)
Production structure of main commercial tree species was studied in a mangrove forest in East Sumatera, Indonesia. This research was carried out in January 1991 using the estimation of standing biomass with stratified clipping method in order to know the production structure of the main commercial tree species in this mangrove forest, i.e. Rhizophora apiculata, Bruguieraparviflora and B. sexangula. The results obtained show that R. apiculata tended to have a sparser foliage of thicker leaves along the stem than B. parviflora or B. sexangula; therefore, R. apiculata is regarded as a shade-intolerant tree species. In contrast, either B. parviflora or B. sexangula tended to have a larger proportion of leaves and branches along the stem; consequently, those species are recognized as shade-tolerant tree species.